Overexpression of the WOX5 gene inhibits shoot development - Kyounghee Lee; Jin Hoon Won; Pil Joon Seo (Plant Signaling & Behavior, 2022)
WUSCHEL-RELATED HOMEOBOX 5 (WOX5) is a member of the WUSCHEL (WUS) homeodomain transcription factor family. WOX5 is expressed mainly in the quiescent center (QC) and confers stem cell identity in the root apical meristem (RAM). Consistent with the role of WUS in repressing root meristem development, we found that ectopic expression of WOX5 disrupted shoot development by repressing shoot-related genes, such as YABBY1 (YAB1). Our findings suggest that WOX5 and WUS potentially confer different tissue identities and specify RAM and SAM, respectively.